PELATIHAN MANAJEMEN HUBUNGAN TENAGA PENJUALAN - Rodhiah; Aritonang R., Lerbin Roberto (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
A sales manager seeks to motivate, empower, and measure the contribution of customer engagement in building and reinforcing increased customer loyalty and retention. Supporting relationship management strategies with the sales team will encourage a comfortable working atmosphere for the sales team and increase motivation in sales efforts. The partners in this activity are engaged in a resin handicraft business located in Serang, Banten. However, they are facing major problems related to sales management strategies. This PKM aims to assist partners in an effort to improve relationship management skills with the sales team. The activity method was conducted through training related to the science of sales relationship management, which was organized online. The results of this activity show that the provision of knowledge about sales relationship management presented in the form of a slide-based presentation (PPT) runs smoothly. Business partners gained the necessary knowledge to improve the role of salespeople in establishing long-term relationships with customers.